Enhancing Early Childhood Educator's Digital Competencies through AI-Powered Learning Modules (AI-PEL) Training Program - Yafie, Evania; Anisa, Nur; Maningtyas, Rosyi Damayani Twinsari; Iriyanto, Tomas; Jumaat, Nurul Farhana; Widiasih, Rina Mukti (Al-Athfal: Jurnal Pendidikan Anak, 2024)
Purpose – Digital skills among educators are becoming increasingly important and essential for creating interactive and relevant learning experiences. However, many teachers are still unprepared to fully integrate technology into their teaching and need to improve their understanding of AI technology to support the learning process. This study aims to determine the effectiveness of improving the digital skills of early childhood education (ECE) teachers through AI-Powered Learning Modules (AI-PEL) training. Design/methods/approach – This research employs a quantitative approach with a quasi-experimental method to evaluate the effectiveness of AI-Powered Learning Modules (AI-PEL) training for Early Childhood Education (ECE) teachers in the Tumpang Sub-district. Purposive sampling was used to select 80 ECE teachers who participated in the training. Data were collected through pre-tests and post-tests. Data analysis involved descriptive statistics using SPSS 17.0, including the Kolmogorov-Smirnov test for normality, Cronbach's Alpha for reliability, and Independent t-tests to compare group means. Findings – This study found a significant improvement in the digital skills of ECE teachers in the Tumpang Sub-district after the AI-PEL training. Initially, the teachers struggled with technology integration, but after the training, their skills and understanding of digital tools improved. Evidence shows that 68 out of 80 participants successfully created teaching modules and picture stories using AI technologies such as Chat GPT, Gemini, DeepL, and Bing Image Creator within the specified deadline. Research implications/limitations – This finding highlights the importance of improving digital skills among teachers, as it enhances their teaching effectiveness and positively impacts students' learning experiences and outcomes. This fosters an engaging, interactive, and effective learning environment in the 21st century. Practical implications – This research emphasizes the importance of supporting strategies such as developing digital learning modules, continuous mentoring, and integrating technology into the ECE curriculum. Partnerships with stakeholders are also crucial to ensuring the sustainability and effectiveness of the AI-Powered Learning Modules (AI-PEL) Training Program. These measures are essential for improving teachers' digital skills and the overall quality of teacher education in the 21st century. Originality/value – This research highlights that early childhood teachers can develop more creative and effective teaching methods with good digital skills. Ultimately, this will improve the quality of early childhood education for the 21st century. Paper type Research paper